The human genome project seen from complexity theory. Bioethical Implications - Sánchez González, Sonia R. (Acta Bioethica, 2008)
In this work, a vision is proposed from a complexity viewpoint about the systematic implications of human genome manipulation. Evolution is the central biological process that helps us understand the diversity of the living world. Today, it is held as the prevalent viewpoint without taking into account that human beings are, in addition to their genetic endowment, products of interaction with their surroundings, as much biological as social. Although it can be of great benefit to humanity, the manipulation of the human genome can also be utilized for discriminatory ends and domination, besides the unforeseeable consequences due to the emergent properties that result from each procedure.